Blood Pressure Is Not Associated With Cerebral Blood Flow in Older Persons. Issue 5 (November 2015) - Foster-Dingley, Jessica C.; Moonen, Justine E.F.; de Craen, Anton J.M.; de Ruijter, Wouter; van der Mast, Roos C.; van der Grond, Jeroen
Abstract : Many studies showing a relation between low blood pressure (BP) and adverse health outcomes in older persons suggest that low BP gives rise to reduced cerebral blood flow (CBF). However, limited evidence is available about this association. Baseline data of 203 participants in the Discontinuation of Antihypertensive Treatment in the Elderly (DANTE) trial were used (mean age, 81 years, using antihypertensive medication and with mild cognitive deficits). BP, BP changes on standing, and CBF derived from pseudo-continuous arterial spin-labeling magnetic resonance imaging were assessed in all participants. In 102 participants who were randomly assigned to 4-month continuation (n=47) or discontinuation of antihypertensive treatment (n=55), BP and CBF change were evaluated at 4-month follow-up. Systolic and diastolic BP were not associated with CBF ( B =−0.21, P =0.50 and B =−1.07, P =0.07), neither were mean arterial pressure, pulse pressure, and BP changes on standing. In subgroups of participants with small vessel–related cerebral pathologies, including high white matter hyperintensity volume, microbleeds, and lacunar infarcts, or in participants with lower cognition or diabetes mellitus, no association was found between any BP parameters and CBF. Furthermore, compared to the continuation group, CBF change at 4 months was not different in the discontinuation group ( B =−0.12, P =0.23). Contrary to the notion that lower BP in old age is associated with decreased CBF, our data do not show this association in older persons using antihypertensive medication and with mild cognitive deficits. Also, this association was not present in subgroups of more vulnerable persons, reflected by small vessel–related cerebral pathologies, lower cognition, or diabetes mellitus. Abstract : Supplemental Digital Content is available in the text.